Cartas para Angola (Laboratório Cisco, 2012)
Brazil and Angola, while on either side of the Atlantic Ocean, have the same language, a common colonial past and many shared stories. In this film, correspondence is exchanged between these two places--some people are longtime friends, others have never met. Their stories intertwine and tell about migration, nostalgia, belonging, war, prejudice, exile and distance. The search for identity and flow of memory are driven by the line of affection that binds the seven pairs of speakers presented in this documentary, people whose life stories are traced between Brazil, Angola and Portugal.